Influence of Bacillus spp culture supplementation through feed or drinking water on the performance of layer chiken - I.P Kompiang (Indonesian Center for Animal Research and Development (ICARD), 2000)
Three thousands 65 weeks old layers were used and divided into 3 groups of 1000 birds, and further divided into 4 sum group (250 birds/group) as treatment replicates, and distributed randomly.Layer in group 1 were fed a basal diet + antibiotic (AB), group 2 were fed a basal diet + 10^9 CFU Bacillus spp culture (PB-M) and group 3 were fed a basal diet and Bacillus spp culture was supplemented in their drinking water (10^9 CFU/litre) (PB-A). The trial was conducted for 14 weeks (2 weeks adaptation period, 10 weeks the feeding treatments, and 2 weeks post treatment, where the AB group continues supplemented with antibiotic, while the PB-M and PB-A group, the Bacillus spp culture supplementation was withdrawned. During the treatment period,% HD production and its FCR of the bird supplemented with Bacillus spp culture were highly significant (P<0.001) better than the one receiving antibiotic. There was no significant different between the PB-M and the PB-A groups. Prosentage HD production and its FCR during post treatment, the birds previously supplemented with Bacillus spp culture were remained significantly better than the one recieving antibiotic. The birds which were previously supplemented with Bacillus spp culture in the feed had significantly (P<0.01) better % HD production and FCR.It is concluded that Bacillus spp culture, could be used to replace antibiotics as a growth promotor, it even gave better results. Key words: Antibiotic, Bacillus spp, layer